The Influence of Islam and Javanese Culture on The Meaning of Keraton Surakarta Hadiningrat’s Architecture - Ihdina Sabili; Murni Rachmawati; Purwanita Setijanti (Institut Teknologi Sepuluh Nopember, 2020)
The effects of religion and culture to the people’s life in Indonesia certainly become inevitability. Keraton, as the residence of the king and the family has philosophical concepts and meanings on each element. Keraton Surakarta in physically and principle adheres to the philosophy of the Javanese people’s life as a media of Islamic development as well as the Javanese culture. This study aims to find out the influence of Islamic values and Javanese culture on the architecture of Keraton Surakarta, especially on the philosophical meaning. The research paradigm used in this study is the Inter-subjective Paradigm. The method applied is Combined Strategies, between Historical Research and Qualitative Research. The data collection was obtained through the literary study, observations, and interview of Keraton Royal Family and The Servants. Research conclusions came from verifying data with interpretation and historiography on the research object. The result of this study is the architectural significance of Keraton Surakarta applying islamic values combined with Java 'cultural philosophy especially to the building orientation and layout sequences. Imprinted meaning derived from the core of the value of human's relationship with god and the courtship philosophy of the Manunggaling kawula gusti.